Depth Profiling of the Near-Surface Layer for Ge33As12Se55 Thin Films - T. N. Shchurova; N. D. Savchenko; K. O. Popovic; N. Yu. Baran (Хімія, фізика та технологія поверхні)
Depth profiles of the near-surface region and chemical composition for amorphous films deposited from Ge33As12Se55 bulk glasses and their changes resulting from six months ageing under ambient conditions have been studied by the methods of Auger electron spectroscopy and X-ray photoelectron spectroscopy. It has been shown that there is a surface layer of about 30 nm thickness enriched with oxygen, germanium, and selenium atoms and depleted of arsenic atoms. It has been found that in the process of natural ageing in the near-surface layer of Ge33As12Se55film the decrease in the relative concentration of germanium and arsenic is observed, with the simultaneous increase in the concentration of selenium and oxygen associated with the formation of As2O3 and GeO2, oxide compounds resulting in а loosening of the surface layer.